2015
DOI: 10.1136/jclinpath-2014-202657
|View full text |Cite|
|
Sign up to set email alerts
|

Protein expression of HER2, 3, 4 in gastric cancer: correlation with clinical features and survival

Abstract: HER3 is correlated with the malignant biological behaviour of GC. Expression of HER3 is a significant predictor of poor survival in GC. Therefore, the development of HER3-targeted agents may provide new possibilities in the treatment of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
(40 reference statements)
4
31
0
4
Order By: Relevance
“…Depending on the presence of these isoforms, HER4 may show different intracellular localizations and varying clinical significance in malignancies. Previous studies on HER4 expression in GC failed to demonstrate a significant association with patients survival [15,39], and little is known about the function of NRG1 in relation to the subcellular distribution of HER4 in GC. In a review of breast cancer studies, while HER4 cytoplasmic expression was favorably associated with patient survival, the significance of HER4 expression localized to the nucleus with regard to survival was uncertain [18].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the presence of these isoforms, HER4 may show different intracellular localizations and varying clinical significance in malignancies. Previous studies on HER4 expression in GC failed to demonstrate a significant association with patients survival [15,39], and little is known about the function of NRG1 in relation to the subcellular distribution of HER4 in GC. In a review of breast cancer studies, while HER4 cytoplasmic expression was favorably associated with patient survival, the significance of HER4 expression localized to the nucleus with regard to survival was uncertain [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies demonstrated that the high expression of certain HER family receptors determined the histological type of cancer (e.g., stomach cancer) [34] and affected patient survival. Furthermore, HER-3 overexpression in stomach cancer aggravated the patients’ condition and reduced their survival [34, 35]. High HER-2 expression in prostate adenocarcinoma was correlated with the serum level of prostate-specific antigen and had an important role in disease progression [36].…”
Section: Role Of Changes In Receptor Expression Density In Health Andmentioning
confidence: 99%
“…HER3 está sobreexpresado en el 87% de los tumores gástricos 15 , y es más común en el citoplasma (64%) que en el núcleo (34%) o la membrana (2%) 6,7 , aunque Choi, et al 15 observaron que HER3 se encuentra principalmente en el núcleo. Para algunos autores, la sobreexpresión de HER3 se relaciona con el subtipo intestinal de CG 6,7,16 , mientras que para otros se relaciona con el subtipo difuso 17 . Por otra parte, también se ha descrito la falta de asociación con algún subtipo de CG 18,19 .…”
Section: Sobreexpresiónunclassified
“…Además, la sobreexpresión se asocia con tumores bien y moderadamente diferenciados, edad avanzada, mayor invasión tumoral, afectación ganglionar, metástasis tumoral y pobre tasa de sobrevida l6, 7,18 . La expresión nuclear de HER3 en el CG se asocia con invasión vascular y linfática, y con baja supervivencia (HER3+ 24-28 meses vs. HER3− 45-47 meses) 6,16 . La expresión de HER4 parece ser mayor en los tejidos gástricos tumorales que en la mucosa gástrica adyacente 6 .…”
Section: Sobreexpresiónunclassified
See 1 more Smart Citation